Electrical power engineering : future trends and development for the Malaysian electrical power industry - 478853 National Conference on Electrical Power Engineering : Future Trends and Development for the Malaysian Power Industry (1991 : Universiti Teknologi Malaysia, K Lumpur) (KL : UTM, 1991)
SESSION I : Penyelesaian masalah dinamik "economic dispatch" sistem kuasa skil besar menggunakan pendekatan "langrangian relazation"/ M.R.A Ghani; M. Ibrahim...[et al] -- "An application of variable truncation dynamic programming to thermal unit committment problem"/ M.S. Salam; A.R. Hamdan...[et al] -- "Algorithm development for the optimal coordination of variable head hydro with thermal plants"/ K.M. Nor; A.H.A Rashid -- "Evaluation of marginal wheeling rates"/ K.S. Loo; S.P. Zhu -- "Performance evaluation of AC load flow techniques"/ A. Mohamed -- SESSION II : "Electricity safety engineering - principles and practice"/ L.S. Wa -- "Tropicalisationn of electrical equipment - design consideration for the electrical engineer"/ Ms L.M. Ling -- "System planning incorporating reliability evaluation"/ F.D. Navaratnam SESSION III(A) : "Secondary resistance control of wound rotor induction motor by thyristor control"/ Soib Taib -- "Selection of development software tool for power electroonic circuit design expert system"/ N. Mariun; M.J.N. Combi...[et al] -- "Resonant mode power supply circuit topologies sdimulation and control/ K.C. Nai; C.F. Foo...[et al] -- "Design methodology of a DC-DC buck converter"/ C.F. Foo; C.C. Choong SESSION IV(A) : "Development of a microprocessor based PWM waveform generator for UPS application"/ A.H.M. Yatim; A. Nawawi...[et al] -- "Power protection in general with special emphasis oon UPS system"/ M. Aykul -- "Off-line flyback power supply using PWM"/ D.C. Patel -- "Power electronic circuits simulation using A simple thyristor switch model in modified SPICE2"/ S. Taib; L.N. Hully...[et L] -- "An intelligent measuring and recording system for power 168 application"/ A.H.M. Yatim; A.A. Razak...[et al] SESSION III(B) : "Introduction of SF6 insulated lead break switches in TNB indoor distribution sustation"/ A.H.A. Bakar -- Penilaian perlakuan perlindungan jarak pada talian penghantaran/ A.A.M. Zin; Z. Azirun -- "Development of symmetrical 3 phase fault calculation for undergraduate studies"/N.A. Rahim; S. Yaakob...[et al] -- "Pembangunan pakej perisian analisis sistem kuasa untuk pengajaran"/ A. Mohamed; A. Hussein...[et al] SESSION IV(B) : "A new attempt to teach power engineering interactively"/ Teo Cheng Yu -- "UTM's ecperience towards the development of a high voltage equipment"/ H. Ahmad; T. Tamsir...[et al] -- "Analisis pengaruh medan elektromagnet voltan tinggi ke atas saluran perhubungan"/ H. Ahmad; A.B. Mohammed -- Condition monitoring of high voltage power equipment"/ S. Shihab, S. Moorthy...[et al]